2012 IEEE 9th International Conference on Mobile Ad-Hoc and Sensor Systems (MASS 2012) 2012
DOI: 10.1109/mass.2012.6502537
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum decision for efficient routing in cognitive radio network

Abstract: Abstract-The cognitive radio (CR) nodes in a cognitive radio network (CRN) do not have license to use specific spectrum band. Instead, they use the spectrum bands of the licensed primary users (PU) without interfering with the PU. When the PU becomes active, interfering CRs should leave to another available spectrum band within the PU's tolerable interference delay (TID). Therefore, CRN operates over wide spectrum bands which span many channels. Since each channel is typically licensed to one PU, this requires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Also, the nodes that are required to perform sensing are known, while not all CR nodes need to sense. In our previous work [7], we empirically showed that this additional time takes usually less than a second.…”
Section: : End Formentioning
confidence: 92%
“…Also, the nodes that are required to perform sensing are known, while not all CR nodes need to sense. In our previous work [7], we empirically showed that this additional time takes usually less than a second.…”
Section: : End Formentioning
confidence: 92%
“…In multiple channel CRN, after one node deciding on the next hop via geographic routing, which channel to use needs to be answered. This problem involves considerations from many aspects, such as minimizing channel switch cost [16], mitigating co-channel interferences [8] etc.. We adopt a lightweight heuristic method in this paper. When there is packet to send and the next hop is decided, packet sender chooses the channel in descending sequence with channel's metric, i.e., likelihood of channel availability, or blocking time.…”
Section: Geographic Routing and Opportunistic Spectrum Accessmentioning
confidence: 99%
“…It is important to note that routing in CR-based networks must generally be considered with the spectrum sensing decision [ 30 , 31 ]. Thus, protocols relevant to routing in CRSNs can generally be categorized as shown below.…”
Section: Recent Studies On Crsn Routingmentioning
confidence: 99%